ASTROFIZIK JARAYONLARNI O‘RGANISHDA YADRO FIZIKASI BILAN FANLARARO INTEGRATSIYANING AHAMIYATI - Xudayberdiyev, E.N.; Samandarov, L.Q. (SCIENCE and SOCIETY, 2021)
This article describes the methodology for analyzing the results of astrophysical studies of the origin, structure and development of the Universe on the basis of interdisciplinary integration in the training of future physics teachers in pedagogical higher educational institutions. It is shown that the interpretation of astrophysical processes from the point of view of quantum mechanics and nuclear physics contributes to the perfect study of their laws and increases the effectiveness of training.